Framing Intellectual and Lived Spaces in Early South Asia: Sources and Boundaries - Cecil, Elizabeth A.; Boer, Lucas den (Beyond Boundaries, 2020)
Frontmatter -- Preface -- Contents -- Introduction -- 1. The Enigma of the Centauress and Her Lover: Investigating a Fifth-century Terracotta Panel from Ahichhatrā -- 2. Visual Story-Telling in Text and Image: The Nāga as Inhabitant of the Cosmic Ocean and the Netherworld -- 3. Vyoman: The Sky is the Limit. On the Bhaviṣyapurāṇa's Reworking of the Liṅgodbhava Myth -- 4. Bronze Temple Bells from the Tibetan Imperial Period: Buddhist Material Culture in Context -- 5. Nonagonistic Discourse in the Early History of Indian Philosophical Debates: From Brahmodyas to the Mahābhāṣya -- 6. The Legitimation of an Authoritative Discourse in Jainism -- 7. Clay Pots, Golden Rings, and Clean Upper Garments: Causality in Jaina Philosophy -- 8. Charting the Geographies of 'Ju Mi pham rnam rgyal rgya mtsho's Perspectivist Approach to the Two Truths -- List of Contributors -- Index